Natural Gas Regulation: An Evaluation of FPC Price Controls - Helms, Robert B.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1974)
This book is structured in Five Chapters. 1) Organization and history of the natural gas industry. 2) History and purpose of field price regulation. 3) The economics of an unregulated gas market. 4) Evaluation of the FPC (Financial Policy Committee) regulation. 5) Reforming field market regulation.
Includes bibliographical references.
ne 20/04/2018
Loan
Keywords: Gas Industry; Natural Gas